Tanggung Jawab Hukum Penyelenggara Dompet Digital di Indonesia - Neng Linda Oktaria (Bhirawa Law Journal, 2026)
Rapid technological advances have transformed the use of payment instruments from physical to electronic, including in Indonesia. In the context of digital wallets, which provide convenience, efficiency, and the benefits of transacting anywhere and anytime, they pose a number of risks such as transaction failure, loss of balance, and even violations of personal data privacy. The problem studied is the legal responsibility of digital wallet operators along with obstacles to transactions in digital wallets and solutions to these obstacles. This study uses a normative juridical research method by examining data derived from secondary data. Based on the results of the study, it is known that this study examines the legal responsibility of digital wallet operators in Indonesia with a normative juridical approach. The results show that responsibility is semi-strict liability, with obstacles in the form of overlapping regulations, low public literacy, and difficulties in proving transactions. Special adaptive regulations and continuous supervision are recommended.